2018
DOI: 10.18089/tms.2018.14si106
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and loyalty in the all-inclusive system in Cape Verde

Abstract: Satisfacción y lealtad en el sistema todo incluido en Cabo Verde AbstractThe aim of this paper is to analyse satisfaction and loyalty in the AllInclusive system in Cape Verde, one of the main destinations of sun and beach in Africa. The methodology used was based on surveys conducted with tourists. The data from this research have been analysed with SPSS 23 and AMOS IBM SPSS 23. The results of this research have shown that in order to achieve the loyalty of tourists, the role of both the agents and those respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…These results were consistent with research conducted by [5,74,86], which reported that tourists visiting Cape Verde were mostly European men, with a high educational level on average. According to our survey, the average age of tourists was lower than that found by [5] i.e., above 40, but some specific forms of tourism could slightly differ from the average international tourist in the destination, especially if we conducted segmented studies, as shown in [87] who referred to all-inclusive tourists in Cape Verde.…”
Section: Characteristics Of the Samplesupporting
confidence: 92%
See 1 more Smart Citation
“…These results were consistent with research conducted by [5,74,86], which reported that tourists visiting Cape Verde were mostly European men, with a high educational level on average. According to our survey, the average age of tourists was lower than that found by [5] i.e., above 40, but some specific forms of tourism could slightly differ from the average international tourist in the destination, especially if we conducted segmented studies, as shown in [87] who referred to all-inclusive tourists in Cape Verde.…”
Section: Characteristics Of the Samplesupporting
confidence: 92%
“…Cape Verde is a country located in the Atlantic Ocean, which is formed by ten islands (nine inhabited and one uninhabited). All together, they contain a total surface area of 4033 km 2 and a total population of around 500,000 persons [74]. As the majority of Small Island Developing States (SIDS), the tourism activity constitutes the main component of the economic structure of Cape Verde, representing 49% of all exports of goods and services [5].…”
Section: Study Sitementioning
confidence: 99%